Knockdown of VEGFR2 inhibits proliferation and induces apoptosis in hemangioma-derived endothelial cells - J.M. Ou; Z.Y. Yu; M.K. Qiu; Y.X. Dai; Q. Dong; J. Shen; X.F. Wang; Y.B. Liu; Z.W. Quan; Z.W. Fei (European Journal of Histochemistry, 2014)
Angiogenesis is a process of development and growth of new capillary blood vessels from pre-existing vessels. Angiogenic growth factors play important roles in the development and maintenance of some malignancies, of which vascular endothelial growth factor (VEGF)/VEGFR2 interactions are involved in proliferation, migration, and survival of many cancer cells. The aim of this study was to investigate the function of VEGFR2 in human hemangiomas (HAs). Using immunohistochemistry assay, we examined the expression levels of VEGF, VEGFR2, Ki-67, glucose transporter-1 (Glut-1), phosphorylated protein kinase B (p-AKT) and p-ERK in different phases of human HAs. Positive expression of VEGF, VEGFR2, Ki-67, Glut-1, p-AKT and p-ERK was significantly increased in proliferating phase HAs, while decreased in involuting phase HAs (P=0.001; P=0.003). In contrast, cell apoptotic indexes were decreased in proliferating phase HAs, but increased in involuting phase HAs (P<0.01). Furthermore, we used small hairpin RNA (shRNA)-mediated VEGFR2 knockdown in primary HA-derived endothelial cells (HemECs) to understand  the  role  of  VEGF/VEGFR2 signaling. Knockdown of VEGFR2 by Lv-shVEGFR2 inhibited cell viability and induced apoptosis in primary HemECs companied with decreased expression of p-AKT, p-ERK, p-p38MAPK and Ki-67 and increased expression of caspase-3 (CAS-3). Overexpression of VEGFR2 promoted cell viability and blocked apoptosis in Lv-VEGFR2-transfected HemECs. Taken together, our findings demonstrate that, increased expression of VEGFR2 is involved in the development of primary HemECs possibly through regulation of the AKT and ERK pathways, suggesting that VEGFR2 may be a potential therapeutic target for HAs.